2017
DOI: 10.1097/bot.0000000000000703
|View full text |Cite
|
Sign up to set email alerts
|

Does Lumbopelvic Fixation Add Stability? A Cadaveric Biomechanical Analysis of an Unstable Pelvic Fracture Model

Abstract: The role of LPF in the treatment of complex sacral fractures is supported, especially in the setting of sacral comminution. LPF with proximal fixation at L4 in a hybrid approach might be needed in highly comminuted cases and when only 1 TI-TS screw is feasible to obtain maximum biomechanical support across the fracture zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…The 6 degrees of freedom of the bilateral ischial tuberosity were constrained [11,12]. A uniformly distributed load (load speed, 10 N/s) of 600 N was applied vertically downward on the upper surface of S1 [13] to calculate model displacement and stress.…”
Section: Analysis Of Model Displacement and Stressmentioning
confidence: 99%
“…The 6 degrees of freedom of the bilateral ischial tuberosity were constrained [11,12]. A uniformly distributed load (load speed, 10 N/s) of 600 N was applied vertically downward on the upper surface of S1 [13] to calculate model displacement and stress.…”
Section: Analysis Of Model Displacement and Stressmentioning
confidence: 99%
“…Beginning with simple percutaneous iliosacral screws for uncomplicated sacrum fractures, the H-shaped sacrum fracture requires sophisticated spinopelvic stabilization with pedicle screws in L4 or L4 and L5 and a sacral-alar-iliac fixation, both of which are connected with a vertical rod. With such a bilateral construct, the applying vertical forces are adequately addressed ( Jazini et al, 2017a ). The armamentarium of spinal surgery also contains the possibility of adding a cross connector to these bilateral rods.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, the complex traumatic sacrum fracture beside the rare entity of spinopelvic discontinuation in severe trauma patients depict utterly different fracture patterns. The traumatic central sacrum fractures are a condition that can be stated generally rare with an incidence of 2 per 100, 000 ( Beckmann and Chinapuvvula, 2017 ), while within pelvic trauma patients, the unstable sacral fracture has an incidence of 17–30% ( Jazini et al, 2017a ). Regarding the operative treatment, complex fractures cannot adequately be reduced by only iliosacral screws but need vertical support and the neutralization of shearing forces ( Guerado et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This even strengthens our conclusion that adhering to the inlet–outlet safe zone as defined here would allow surgeons to safely insert more than one screw in S1. This is especially important since numerous studies have shown that multiple sacral screws provide the strongest biomechanical fixation …”
Section: Discussionmentioning
confidence: 99%